CORRELATION OF ORAL HYGIENE KNOWLEDGE AND PRACTICE AMONG UNDERGRADUATE DENTAL STUDENTS - Afeera Khan; Zulfqar, Asma; Qureshi, Beenish (Journal of Postgraduate Medical Institute, 2022)
Objective: To assess the correlation between oral hygiene knowledge and practice among undergraduate dental students. Methodology: This cross-sectional study was conducted among undergraduate dental students at the dental section of Islamabad medical and dental college over three months. Data for this study was collected using a pre-piloted questionnaire. The collected data were encoded, entered, and analyzed using Statistical Package for Social Statistics version 21.0. Spearman test was used to find the correlation of qualitative variables. P-value 0.05 was considered statistically significant. Results: A total of 188 undergraduate dental students were contacted to participate in the study. Out of these, 176 (93.6%) returned completely filled questionnaires. The results were calculated using the Spearman test which showed that the correlation in "oral hygiene knowledge and practice among students was insignificant (r=0.096, p= 0.207). Conclusion: In our study dental students showed a lack of oral self-hygiene practice during their undergraduate period. It is recommended that in addition to spreading awareness regarding oral hygiene; the practice of oral hygiene should also be stressed.